Aon Hewitt's 2013 trends in global engagement: where do organizations need to focus attention?. Issue 1 (2014) - ,
Abstract : Purpose – The purpose of this paper is to highlight the key trends in the levels and drivers of employee engagement over the past 12 months. It proposes some key steps for HR professionals to take in helping leaders to keep focused on those issues that will make the biggest difference to employee motivation.Design/methodology/approach – The paper is based on Aon Hewitt's definition and model of employee engagement and the most recent analysis of trends from its database of more than 7, 000 organizations representing 18.6 million employees. A subset of this database is the "Best Employer" group of companies, which includes organizations that have passed thresholds after analysis of employee engagement scores, HR practices, CEO interviews and financial performance.Findings – Engaging the right employees in demonstrating the right behaviors remains a critical ingredient for companies looking to raise performance levels in today's challenging economic conditions. Global engagement levels have increased slightly over the past year but four out of ten employees are still not engaged. There are some key areas to focus on in terms of action that have been proven to make a difference in organizations with high levels of engagement.Originality/value – HR can play an important role in ensuring that organizations keep focused on those aspects of the work environment that can make the biggest difference to employee engagement and business performance. The function's added value comes through support and guidance with engagement driver areas, such as career development, rewards, recognition and pay, and also in terms of securing return on organizational investment in employee research by making sure engagement is not just seen as the "annual survey".